Developing a Professional Philosophy for Applied Exercise Psychology: Integrating Theory and Practice. Issue 3 (2nd July 2020) - Castillo, Elmer A.
Abstract: Professional philosophy has become a topic of great interest within the sport psychology literature. However, professional philosophy for applied exercise psychology has not yet been clearly established as a specific line of applied or research interest. This reflective paper aims to fill this void by promoting awareness of how professional philosophy can be used to guide exercise psychology practice and evaluating a case study involving the application of professional philosophy within an exercise context. A prominent model of professional philosophy for sport psychology service delivery is discussed in relation to applied exercise psychology along with corresponding examples of each of the levels along the model's hierarchy specific to exercise psychology. Taken together, this serves as the reflective foundation from which applied implications are discussed.